KONTRIBUSI DAYA LEDAK OTOT TUNGKAI DAN KOORDINASI MATA DAN KAKI DENGAN AKURASI SHOOTING SSB PATRIOT MUDA KUOK - Pratama, Aldo Azmi; ', Saripin; Vai, Aref (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Based on observations on a player School Football Patriot Muda Kuok that shooting players who follow exercise football still not good, it is revealed that limited capability players especially in doing shooting who directed and effectively who is in what. The purpose of this research is to know how big contribution explosive power limb muscles and coordination eyes and feet with accuracy shooting in School Football Patriot Muda Kuok. Population in this study a whole object research, namely soccer players players school football patriot young kuok, consisting of 18 people, by using total of sampling, so sample in this research was 18 people. An instrument too was vertical synchronization jump, coordination eyes and feet and test shooting. Data obtained in analysis with employing correlation product moment, To determine contribution used the coefficients determinan. Of the results obtained explosive power limb muscles have become with accuracy shooting in Schools Football Patriot Muda Kuok is as much as 25,81 %. Of the results obtained coordination the ankles have become with accuracy shooting in School Football Patriot Muda Kuok 32,26 % as much as. There were the contribution of jointly between explosive power limb muscles and coordination the eye the foot against the accuracy of the shooting scene in schools football young patriot kuok 34,69 % as much as.Keywords: Explosive Power Limb Muscles, Coordination ankle, accuracy shooting